Problem Area Formation as an Element of Computer Aided Diagnosis: A Comparison of Two Strategies Within Quick Medical Reference (QMR) - Berman, L.; Miller, R. A. (Methods of Information in Medicine, 1991)
INTERNIST-I’s use of “partitioning” to group related diagnoses into problem areas (for competitive consideration and elimination during case analysis) is felt to be the source of many of its strengths as well as some of its weaknesses. QMR, INTERNIST-I’s successor program, embodies a homology function which can act as an alternative to the partitioner for problem area formation. This study undertakes a comparison of the problem areas generated by the INTERNIST-I partitioning algorithm, the QMR homology function, and expert clinicians; it finds the correlation to be poor. The authors then discuss another method of problem area formation which might better mimic a human clinician and provide an alternative approach in diagnostic computer-aided decision making.
Keywords: Computer-Assisted Medical Diagnosis; Problem Area Formulation; Quick Medical Reference (QMR); Evaluation of Decision-Making Strategy